Implementation of The Apriori Algorithm Method to Analyze the Pattern of Motorcycle Sales at PT. Alpha Scorpio - Oloan Sihombing; Veronica T. D. Simamora; Vivian P. Leo; Petrus Kristian P. Marpaung (Paradigma, 2022)
This study discusses how to make a pattern in the motorcycle sales process, where every month the sales of each type of motorcycle must be different. So that every employee is overwhelmed in classifying the types of items that will be recommended in adding stock. The goal is to keep consumer demand met every month. Based on the research that has been done, this study concludes: the results of research with a minimum support limit of 30% and a minimum confidence of 70%, form 20 rules every year. One of the rules established is that if a 2X4 motorcycle is sold, the Yamaha A 90 type is sold with a support value of 45% and a confidence value of 74.46%.This study discusses how to make a pattern in the motorcycle sales process, where every month the sales of each type of motorcycle must be different. So that every employee is overwhelmed in classifying the types of items that will be recommended in adding stock. The goal is to keep consumer demand met every month. Based on the research that has been done, this study concludes: the results of research with a minimum support limit of 30% and a minimum confidence of 70%, form 20 rules every year. One of the rules established is that if a 2X4 motorcycle is sold, the Yamaha A 90 type is sold with a support value of 45% and a confidence value of 74.46%.